FLOUTING MAXIMS IN STAND-UP COMEDY ACT BY SIERRA KATOW: A PRAGMATICS STUDY - PUSPA ARTIKASARI, ELVERA (LANGUAGE HORIZON, 2019)
Maxims was a principle must be applied in the communication process. According to Grice (1975), there were 4 maxims that must be obeyed in the communication process so that the process runs smoothly: quality, quantity, relation, and manner. In creating humor, a comic flouted one or more maxims. Analyzing flouting maxims in stand-up comedy would be interesting because a comic would flout maxims without any communication process in accordance with the purposes of this research. This study used qualitative method to answer research questions. The qualitative method was chosen as a methodology for analyzing data findings because it was the most suitable method for answering research questions. This research uses Grice theory to analyze utterance in stand-up comedy by Sierra Katow. The results of this study are as follows: (1) there were 4 types of flouting maxims that could be found in stand-up comedy act by Sierra Katow such as flouting maxim of quantity, quality, relation, and manner; (2) there were 7 of 11 types of humor that could be found in stand-up comedy act by Sierra Katow such as irony, satire, sarcasm, overstatement and understatement, self-deprecation, teasing, and double entendres; (3) there were 3 mechanisms of flouting maxims created humorous sense in stand-up comedy act by Sierra Katow such as incongruity, hostility, and release. In conclusion, Sierra flouted the maxims using 3 mechanisms and the flouting maxims have created on those 7 types of humor. In addition, there were 3 mechanism of creating humor (incongruity, hostility, and release) by flouting maxims of those 3 mechanisms.